2007
DOI: 10.1080/08860220701460137
|View full text |Cite
|
Sign up to set email alerts
|

Do AshSplit Haemodialysis Catheters Provide Better Flow Rates in the Long Term?

Abstract: Background. Recently, interventional radiologists have adopted an increasingly prominent role in the placement and management of hemodialysis catheters, as well as in the research and development of new and better catheters. The purpose of this study was to evaluate the viability and hemodialysis efficiency of the AshSplit catheter and the Permcath catheter. Methods. 204 consecutive patients requiring radiological insertion of hemodialysis catheters were followed, retrospectively, over a 42-month period. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…In contrast, Trerotola et al 18 reported a significant survival benefit instead for split-tip compared with step-tip catheters (P ¼ .022). However, Keeling et al 13 reported no statistical difference (P ¼ .498) in catheter survival curves for step-and split-tip catheters.…”
Section: Catheter Survival Timementioning
confidence: 97%
See 4 more Smart Citations
“…In contrast, Trerotola et al 18 reported a significant survival benefit instead for split-tip compared with step-tip catheters (P ¼ .022). However, Keeling et al 13 reported no statistical difference (P ¼ .498) in catheter survival curves for step-and split-tip catheters.…”
Section: Catheter Survival Timementioning
confidence: 97%
“…Thus, eight studies were eligible for inclusion in this meta-analysis. 6,[12][13][14][15][16][17][18] These eight studies were published between 1999 and 2014. Four studies recruited patients using step-tip or split-tip tunneled HD catheters.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations